Jitteriness/Anxiety Syndrome Developing Immediately following Initiation of Oral Administration of Sertraline - Nakamura, Toshinori; Sugiyama, Nobuhiro; Sasayama, Daimei; Hagiwara, Tetsuya; Washizuka, Shinsuke (Case Reports in Psychiatry, 2017)
Here, we report our experience with patients in whom jitteriness/anxiety syndrome developed immediately following the start of oral sertraline administration. Administration was discontinued in these patients on day 2, and the jitteriness/anxiety syndrome improved the following day. Jitteriness/anxiety syndrome may develop immediately following oral administration of even low doses of sertraline, and improvement can be expected if sertraline is promptly discontinued.